PROGRAM REMAJA BIJAK DALAM PENCEGAHAN PERNIKAHAN DINI - Ns., M.Kep., Ferawati; Kurniati, S.Kep.,Ns., M.Kep., Mei; S.Kep., Ns., M.Kes., Yusuf; Anniza Pramesti, S.Kep., Ns., Adhe; Nurfitriani, S.Kep., Ns. , Yuzita (LPPM ISTeK ICsada Bojonegoro, 2024)
24 Marriage is a physical and spiritual bond between a man and a woman as husband and wife with the aim of forming a happy family physically and mentally and eternally based on the Almighty Godhead. Based on data from UNICEF Indonesia in 2020, it shows that the prevalence of child marriage in Indonesia in 2018 was 11.21% of children married before 18 years, 0.56% of children married before 15 years. If a girl aged 10-14 years is pregnant, she has a fivefold risk of dying during pregnancy/giving birth. This is caused by the physiologic anatomy of girls who are not yet ready to conceive and give birth. Early marriage can also increase the risk of stunting in children, because people are not ready to take a role in the child's growth and development process, apart from that, mentally underage women are not ready and have the potential for violence resulting in divorce. This time, the Assisted Family Program is targeted at Bulu Village, Balen District, Bojonegoro Regency, by focusing activities on teenagers. Fostered Families focus on 36 partner families which include teenagers aged 12-19 years. This activity lasted for 6 meetings. The activity begins with an initial assessment related to health status, independence, and nursing care to drug therapy. After that, it was continued with providing health education regarding adolescent problems as well as showing educational creative videos with the title